Dux, Un Progetto Editoriale - Sándor, Krisztina (Italogramma, 2025)
This work is the summary of a research carried out at the Sarfatti Foundation archive at the Mart museum of Rovereto. The research focused specifically on Margherita Sarfatti's correspondence prior to the composition of Dux with Giovanni Prezzolini and on the letters written by Margherita to the publishing houses, translators and book distributors at the time of the publication of Benito Mussolini's biography. The examined documents revealed that the book Dux was not merely an additional element of Mussolini’s propaganda, but also a well-structured publishing project conceived and executed with great care by Margherita Sarfatti. The result of the remarkable effort of the author herself and the publishing houses was a best seller that sold thousands of copies, not only in Italy but also in many other countries around the world.